Dual Enrolment in Elementary Schools of Jharkhand - Singh, Chandra B.P. (INDIAN EDUCATIONAL REVIEW, 2025)
Dual enrolment refers to double entry of the same student in two separate school enrolment registers. The study was conducted in a tribal district of Jharkhand state. It was a multi-layered sample covering both the government as well as the private unrecognised schools of one cluster selected on the basis of U-DISE report (2014). 23 schools (15 governments and 8 private schools) were taken into consideration for the study. Altogether 166 dual enrolments out of 4743 enrolments were evident in the admission register of the government schools constituting about 3.5 per cent inflation in the total enrolment. Only 95 cases of dual enrolments out of 955 enrolments were recorded in the unrecognised private schools sharing about 10 per cent inflation in the total admission. Primary schools experienced more cases of dual enrolment followed by middle schools. Highest concentration of dual enrolment was recorded in Class IV (7.64) followed by Class III (7.29). Minimum cases were observed in Class VIII (2.47) and Class VII (3.80). An overall per cent of dual enrolment was 5.42 substantiating the inflation in the volume of enrolment of the government schools. The study discussed possible dynamics of dual enrolment.